The Influence Of Promotion And Location On The Increase In The Number Of Consumers At Grand Kartika Restaurant - Sri Putri Candeny Zebua; Yuterlin Zalukhu; Maria Magdalena Bate’e; Eliyunus Waruwu (UNIVED Press, 2024)
This study aims to identify the impact of promotion and location on the increase in the number of consumers at Grand Kartika Restaurant. The method used is a survey. The research population includes visitors and service users of Grand Kartika Restaurant from March to May 2024. The research sample consists of 69 respondents collected through questionnaires. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS Version 22 software. The results of the study show that both promotion and location have a positive effect on the increase in the number of visitors to Grand Kartika Restaurant. KEYWORDS promotion, location, increase in the number of consumers